Ion transport by the Na-Ca exchange in isolated rod outer segments. - Lagnado, L (1988)
The inward membrane current generated by the coupled exchange of external sodium for internal calcium has been investigated in isolated rod outer segments. The exchange rate is sensitive to voltage, with a reduction by a factor of e occurring for a 70-mV depolarization in normal Ringer's solution. The voltage sensitivity is not a constant property of the exchange, as it is reduced by an increase in external Na+ or by the removal of external Ca2+, Mg2+, or K+. Changes in membrane potential do not appear to affect the affinity of the exchange mechanism for internal Ca2+, but hyperpolarization increases the affinity for external Na+. When the external Na+ concentration is raised sufficiently to saturate the exchange mechanism, the voltage sensitivity is no longer apparent. We propose that the voltage dependence of the exchange is due to the external Na+-binding site being sensitive to membrane potential, perhaps because it is located within the membrane electric field.